Imaginario colectivo popular del construir vivienda informal en la ciudad de Bogotá (2020)
The article identifies the relationship between popular collective imagination and informal housing. In the case of the city of Bogotá, it is important to emphasize the house-to-house model as a tool to build informal territory. It is a flexible and organic mechanism capable of integrating the popular collective imagination with the pre-existence of the context where it happens, and therefore teach us to overcome the social / social segregation that characterizes Latin American cities. For this purpose, the main objective is to identify the social and spatial patterns of the construction of informal housing in the city of Bogotá. In this sense, the methodological strategies of the investigation are confirmed by the analysis from the phenomenological perspective that allows to present theoretical explanations. It is concluded that the understanding of the popular collective imagination is an instrument for the study of the improvement of the habitat conditions in informal dwellings